Animaker Animation Video Design as a Digital-Based Learning Media with the Theme of Comparison and Scale in Elementary School - Yuan Anisa; Meilisa Malik; Tantri Octora Dwi Syah Putri; Muhammad Hafiz; Nanda Novita (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aimed to determine the effectiveness of developing digital-based teaching materials in Animaker-assisted animated videos aimed at grade V elementary school students on Comparison and Scale subject matter. This was done because problems often arise regarding the effectiveness of the teaching and learning process. Teachers have also been required to be active and creative in developing learning systems in the classroom that coexist with technological advances. In this study, the learning system developed is on teaching materials. This researcher uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research is subjected to elementary school students in Langkat Regency. Data collection is done using assessments by material experts, media experts, homeroom teachers, and students. Overall based on media experts reached 81.25%, material experts reached 81.25%, homeroom teachers reached an average of 82%, and the average student response of 87% was classified as high so that it could be stated that Animaker-based animation videos on Comparison and Scale materials were feasible to be used as teaching material facilities in the classroom.